Alveolar Bone Grafting: Donor Site Review of 100 Consecutive Cases in Cleft Lip and Palate. (March 2017) - Amin, Kavit; Khor, Wee Sim; Rosich-Medina, Anais; Beale, Victoria
Objective: Review of patients who underwent secondary alveolar bone grafting for total inpatient stay, postoperative complications, and postoperative analgesic requirements. Design: Retrospective analysis of medical records. Setting: Tertiary care center as part of a regional cleft lip and palate network. Patients: All patients who underwent secondary alveolar bone grafting from the iliac crest. Interventions: Local anesthetic was infiltrated overlying the anterior iliac crest. An incision was made to conform to the future skin crease and avoid muscle dissection. The cartilaginous cap was incised and raised, and cancellous bone was then harvested. The cavity was packed with hemostatic cellulose and closed in layers. All patients received postoperative antibiotics. All patients were prescribed regular paracetamol (acetaminophen) and ibuprofen if there were no contraindications. Oral morphine was available when requested. Main Outcome Measures: Length of stay, postoperative analgesic requirements, and postoperative donor site and oral complications. Results: From 100 consecutive patients, 92 (92%) of the patients were discharged the day after surgery; one (1%) patient required four nights of monitoring for postoperative pyrexia of unknown origin. All patients received regular paracetamol, and the majority (86%) did not require oral morphine. Complications included seroma (4%), superficial donor site abscess (1%), postoperative pyrexia of unknown origin (2%), gingival bleeding (2%), and oral infection (2%). Conclusion: The findings suggest that donor site pain may be well controlled with simple, regular analgesia. Children tolerated this procedure well and were safely discharged the day after surgery. Alveolar bone grafting from the iliac crest was found to have low complication rates.